1989
DOI: 10.1159/000226694
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Thyroglobulin Level Determination to Follow Up Patients with Highly Differentiated Thyroid Cancer

Abstract: The highly differentiated thyroid tumours account for 0.80% of all human malignancies. The papillary and follicular tumour tissues of this tumour type are relatively benign, hormone-dependent and beside their treatment specificity they secrete the tumour-specific thyroglobulin. This it becomes possible to follow the development of metastases, the effectiveness of therapy applied as well as the history of the disease. The authors studied the change of thyroglobulin level in 153 patients with highly differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The conclusion from previous series that aneuploid cancers may have a worse prognosis than diploid cancers could be explained by the age of the patients. In the present study the high incidence of aneuploid cancers (27%) compared to common papillary carcinomas could reflect the aggressiveness of these tumors as well as the age distribution [21,23].…”
Section: Biologic Characteristicsmentioning
confidence: 61%
See 1 more Smart Citation
“…The conclusion from previous series that aneuploid cancers may have a worse prognosis than diploid cancers could be explained by the age of the patients. In the present study the high incidence of aneuploid cancers (27%) compared to common papillary carcinomas could reflect the aggressiveness of these tumors as well as the age distribution [21,23].…”
Section: Biologic Characteristicsmentioning
confidence: 61%
“…The value of DNA as a prognostic indicator in thyroid cancer has not been confirmed. It has been suggested that diploid DNA content is of prognostic value [21,22], but it has not been clearly shown whether it is the ploidy that decides the prognosis of the patient or the fact that patients have been treated differently [23].…”
Section: Biologic Characteristicsmentioning
confidence: 99%